Identification and Functional Analysis of Novel Mutations in AXIN2 and LRP6 Linked With Non‐Syndromic Tooth Agenesis - Wendi Luo; Haitang Yue; Guangtai Song; Jing Cheng; Miao He (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Tooth agenesis (TA) ranks among the most common dental abnormalities. This study aimed to explore the etiology and pathogenesis in Chinese families with non‐syndromic TA. Methods Chinese families exhibiting non‐syndromic TA were recruited. Exome sequencing was conducted to identify mutations in the candidate genes, followed by Sanger sequencing for validation. Functional studies, including bioinformatics analyses, western blots, and dual‐luciferase assays, were performed to analyze the impact of the two mutations on the Wnt/β‐catenin pathway. Results We identified a novel heterozygous frameshift insertion in AXIN2 [NM_001363813.1: c.1799dupG (p.Asn601GlnfsTer41)] and a novel de novo heterozygous non‐frameshift deletion in LRP6 [NM_002336.3: c.3074_3082del (p.1025_1028del)]. Further functional studies indicated that AXIN2 p.Asn601GlnfsTer41 caused hyperactivation of the Wnt/β‐catenin pathway, and LRP6 p.1025_1028del led to pathway suppression. Conclusions This study expands the spectrum of AXIN2 and LRP6 mutations associated with non‐syndromic TA. Our study provided further functional evidence supporting the pathogenicity of suppression and excessive activation of the Wnt signaling pathway in TA.